Morphological study of the spectrum of lesions encountered in the heart and coronaries on autopsy - Md Ibrahim Siddiqui; Anita A Mahanta; S R Umesh; Saara Neeha; Sainath K Andola (Wolters Kluwer Medknow Publications, 2022)
Background and Objectives: This research study has been carried out to study the various morphological changes in the heart in medicolegal autopsies and to compile data for the frequency of heart diseases found in autopsy cases. Methods: The present study comprised 430 medicolegal autopsy cases. Details of the cases were entered in a proforma prepared for the study. The heart was fixed in 10% formalin, and then, opened along the flow of blood. The findings were based on gross and microscopic examinations. Results: Out of 430 adult hearts, 211 (49.0%) cases showed 253 cardiac lesions; 35 (8.1%) cases of coronary atherosclerosis and 196 (45.5%) aortic atherosclerosis were noted; 7 cases of ischemic lesions (1.6%) were identified; 12 (2.7%) cases of hypertrophy; 2 cases of valve calcification; and 1 of cardiomyopathy were noted. Conclusion: In the present study, among medicolegal autopsies, atherosclerotic disease was the most frequently encountered lesion followed by hypertrophy. The incidence of atherosclerosis was found to be 47.6%. This study shows the high prevalence of atherosclerosis in the population.